Parental involvement and support of selected parents for children with special needs: a case study - Sheela Marasigan-Pagkalinawan; Wilson Cordova (Universidade Estadual de Alagoas, 2024)
The purpose of the study was to determine the extent of parental involvement with respect to guiding, communication, home training and attending meetings/conferences in the school. As well as parental support with respect to financial, psychological, and emotional aspects were used. This study made use of the descriptive methods of research. The questionnaire-checklist developed and subjected to validation of experts in the field of research and education. The subject-respondents of the study were the 40 parents and 3 Special Education teachers who were chosen through stratified random sampling. Regarding the assessment of the respondents, parental involvement components such as Guiding, Communicating, Home Training and Attending Meeting/School Conference that affected the learner's performance were assessed often by the parents. Among the four, Attending Meeting/School Conference had a notable mean of 6.35 verbally interpreted as Often. In terms of parental support Financial, Emotional and Psychological aspects, they gained Often as elicited by the parents toward their child. Among the three, the financial aspect had the notable mean of 3.67 verbally interpreted as Often. There was no significant difference on the assessments of the two groups of respondents on the extent of parental involvement since the t-value did not exceed the 0.05 level of significance which failed to reject the null hypothesis. However, there was a significant difference on the assessment of the two groups of respondents on parental support and psychological aspect and no significant difference on financial and emotional aspect. Lastly, the School Improvement Plan and Annual Implementation Plan carried out involvement programs engaging parents and other stakeholders.